Prognostic significance of extranodal extension of regional lymph node metastasis in papillary thyroid cancer. Issue 9 (29th October 2014) - Wu, Ming‐Hsun; Shen, Wen T.; Gosnell, Jessica; Duh, Quan‐Yang
Abstract Background The presence and location of regional lymph node metastasis affect the prognosis of patients with thyroid cancer. Lymph node classification of the current TNM system may be inadequate because it insufficiently characterizes the nature and severity of lymph node metastasis that may influence prognosis. Methods We retrospectively studied 240 patients with papillary thyroid cancer and node metastases who had undergone total thyroidectomy, lymph node dissection, and postoperative 131I treatment at the University Cancer Center between 1994 and 2004. We reviewed the status of regional lymph node metastasis, including the location, number, largest size, and extranodal tumor extension and analyzed their effect on the prognosis of the patients. Results There were 172 women and 68 men, with a median age of 38 years and median tumor size of 1.9 cm. Thirty‐five percent had only central compartment (N1a) nodal metastasis and 65% had involvement of both central and lateral compartments (N1b). There were a median of 4 nodes containing metastasis with a median largest diameter of 1.2 cm. Sixty patients (25%) had extranodal extension of cancer. Multivariate analysis showed that patient age (p = .0017; hazard ratio [HR], 2.156), >3 lymph node metastasis (p = .0316; HR, 1.806), and extranodal extension (p < .0001; HR, 4.027) were independent predictors of disease recurrence. Patient age (p = .0034; HR, 22.068), vascular invasion (p = .01; HR, 8.2), and extranodal extension (p = .022; HR, 12.597) were independent predictors of disease‐specific survival (DSS). The DSS and recurrence‐free survival curve between patients with and without extranodal extension differ significantly (p < .0001). For those older than 45 years, the 10‐year recurrence was 11 of 43 patients for those without extranodal extension and 24 of 27 patients for those with extranodal extension (p < .001). Among patients with stage 4a/4b, those with extranodal extension had a significantly worse DSS and disease‐free survival (DFS; p < .001) than those without extranodal extension. The prognosis of patients with stage 4a/4b cancer who had no extranodal extension was the same as patients with stage 3 cancer. The status of extranodal extension seems to be a stronger prognostic predictor than the location of metastatic lymph nodes (N1a/1b). Conclusion Presence of extranodal extension of metastatic nodes is a significant adverse independent prognostic factor for patients with lymph node metastasis from papillary cancer. This may need to be considered in future updates of the TNM system for thyroid cancer. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1336–1343, 2015